2018
DOI: 10.1080/03639045.2018.1515219
|View full text |Cite
|
Sign up to set email alerts
|

Application of liquisolid technology for promoting the renoprotective efficacy of walnut extracts in chronic renal failure rat model

Abstract: Chronic renal failure (CRF) is among the major health problems that could lead to increased morbidity and mortality among population. 'Nutraceuticals' is an emerging field for natural agents from plant foods that could reduce the progression of such disease. Many newly developed drugs are having bioavailability problems owing to their water insolubility. Liquisolid technique is one of the promising technological approaches to increase solubility and hence, drug absorption. The aim of the present research is to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Nephrotoxicity may originate as an adverse reaction against non-steroidal anti-inflammatory drugs, some antibiotics, antineoplastic agents, or xenobiotics ( 3 4 5 ). Therefore, It is of high importance to keep the kidney healthy for all people affected by kidney diseases ( 6 ), besides, it has been very crucial to scout for new nephroprotective agents to improve renal function, renal tissue healing, and regeneration ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…Nephrotoxicity may originate as an adverse reaction against non-steroidal anti-inflammatory drugs, some antibiotics, antineoplastic agents, or xenobiotics ( 3 4 5 ). Therefore, It is of high importance to keep the kidney healthy for all people affected by kidney diseases ( 6 ), besides, it has been very crucial to scout for new nephroprotective agents to improve renal function, renal tissue healing, and regeneration ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…The owability of the effervescent powder is mainly evaluated by different parameters such as bulk density, tapped density, Carr's compressibility index, Hausner ratio and angle of repose [50,51].The bulk density and tapped density of the prepared orange avoured effervescent powder were 0.29 ± 0.01 and 0.35 ± 0.01 g/mL, respectively. It has been reported that a powder with Carr's compressibility index and Hausner ratio lower than 20% and 1.25, respectively is considered to be free owable [52].…”
Section: Physical Properties Of the Orange Avoured Effervescent Powdermentioning
confidence: 99%